The Presidentialization of Political Parties in Russia, Kazakhstan and Belarus - Glaser, Marina; Krivushin, Ivan.; Morini, Mara. (Cham : Springer Nature Switzerland : Imprint: Palgrave Macmillan, 2023)
This book analyses the presidentialization of parties in three countries of the post-Soviet space - Russia, Belarus and Kazakhstan - and the role of this phenomenon in their recent political history. The concept of presidentialization of politics means that parties tend to adjust by becoming 'presidentialised' in the sense that parties delegate their leaders-as- Presidents to shape both their electoral and governing strategies. The presidentialization of parties refers to institutional resources, constraints and opportunities. It can be also described both as centralization of leadership and a style of government, overlapping with that of personalization of politics that it consists of personal characteristics, attitudes, personal capital and charisma in making politics, instead. Since their introduction, the concept of presidentialization have been mostly analysed within the Western or other democratic countries. Very little attention, however, has been paid to the phenomenon presidentialization of political parties in non-democratic countries or in countries with a transitional form of government . This volume enhances our theoretical understanding of the political role of the Presidents of Russia, Kazakhstan and Belarus in controlling the legislative space and elected officials. Marina Glaser is Professor of Philosophy, Department of International Relations, HSE University, Moscow, Russia. Ivan Krivushin is Professor of Modern History, Department of International Relations, HSE University, Moscow, Russia. Mara Morini is Associate Professor, PhD in Political Science, Department of Political and International Sciences (DISPI), University of Genoa, Italy.
Chapter 1: The Presidentialisation and the party of power in Post-Soviet States -- Chapter 2: The presidentialisation of Russian political parties -- Chapter 3: The presidentialisation of Belarus political parties -- Chapter 4: The presidentialisation of Kazakh political parties -- Chapter 5: The presidentialisation in Post-Soviet States: theoretical challenges.
Keywords: Europe -- Politics and government; Political leadership; Legislation; European Politics; Political Leadership; Legislative Politics